Determinants of FTTH tariffs: an empirical EU study - Elias Aravantinos; Konstantin Petre; Dimitris Katsianis; Dimitris Varoutas (International Telecommunications Society (ITS), 2020)
This study examines the relevant factors that determine the FTTH tariffs within the European Union (EU) zone. FTTH networks, as a relevant new technology, have a significant impact on modern economies. This is reflected by their adoption and use across EU countries along with the increasing deployment. However, FTTH tariffs, play an important role in the technology's adoption, as they are driven both by the level of adoption and the market's competition. Looking at the EU countries between 2013 and 2018, we find a consistent effect of FTTH tariffs on national economic output with diminishing returns to scale. The study reveals that market player's competition is a moderator parameter on FTTH tariffs, in addition to the technology's adoption. Finally, FTTH tariffs tend to drop overall during the study's period across all the EU countries, motivating more residents to have access to high speed Internet and develop new applications. Hence, EU countries could achieve faster their goals, with subscribers' willingness to pay for high speed service with the right market competition and service offering in place, towards the 2020 national broadband plan regarding ultrafast connectivity.
Keywords: 330; FTTH; FTTP; Tariffs; NGA Broadband; Forecasting